Accounting for the management of the activities of tourist enterprises as a means of achieving the goals of sustainable development - I.V.; V.A.; K.S. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The development of tourism without causing harm to the surrounding natural environment, the so-called sustainable tourism, is an integral part of the sustainable development of society, which can ensure powerful harmonious development of territories. Sustainable development in the tourism industry means a harmonious combination of ecological, socio-cultural and economic factors of tourism, which are implemented in parallel with cultural and ecological development, maximally excluding harmful effects on natural ecosystems. Taking into account the negative impact of tourism on the surrounding natural environment, the issue of implementing the provisions of the concept of sustainable development in the activities of tourist enterprises requires additional research. The purpose of the study is to develop theoretical and organizational and methodological provisions of accounting in tourist enterprises as a means of achieving the goals of sustainable development, which will contribute to the growth of their investment attractiveness in the post-war period. In order to develop the tourism industry in accordance with the concept of sustainable development, it is advisable to develop and implement environmentally-oriented business management based on accounting information. It is proposed to include expenditure items related to environmental protection in the financial accounts of tourist enterprises. Such actions are aimed at the search for more ecologically sound directions for the development of tourist activity, which, in turn, can ensure a more rational use of natural resources and determine methods of restoration of damaged natural territories and objects. The implementation of the above proposals on record keeping and reporting by tourist enterprises will contribute to the information provision of interested users and will allow the creation of an environmental management system of the enterprise, as well as an effective environmental policy in tourism activities, aimed at minimizing the negative impact of tourism on the state of natural ecosystems, which will contribute to the growth of their investment attractiveness in the post-war period.